Thoughtflow: Standards and Tools for Provenance Capture and Workflow Definition to Support Model‐Informed Drug Discovery and Development. (15th May 2017) - Wilkins, JJ; Chan, PLS; Chard, J; Smith, G; Smith, MK; Beer, M; Dunn, A; Flandorfer, C; Franklin, C; Gomeni, R; Harnisch, L; Kaye, R; et al.
Abstract : Pharmacometric analyses are complex and multifactorial. It is essential to check, track, and document the vast amounts of data and metadata that are generated during these analyses (and the relationships between them) in order to comply with regulations, support quality control, auditing, and reporting. It is, however, challenging, tedious, error‐prone, and time‐consuming, and diverts pharmacometricians from the more useful business of doing science. Automating this process would save time, reduce transcriptional errors, support the retention and transfer of knowledge, encourage good practice, and help ensure that pharmacometric analyses appropriately impact decisions. The ability to document, communicate, and reconstruct a complete pharmacometric analysis using an open standard would have considerable benefits. In this article, the Innovative Medicines Initiative (IMI) Drug Disease Model Resources (DDMoRe) consortium proposes a set of standards to facilitate the capture, storage, and reporting of knowledge (including assumptions and decisions) in the context of model‐informed drug discovery and development (MID3), as well as to support reproducibility: "Thoughtflow." A prototype software implementation is provided.